2020
DOI: 10.1007/s11101-020-09661-0
|View full text |Cite
|
Sign up to set email alerts
|

Saponins as cytotoxic agents: an update (2010–2018). Part I—steroidal saponins

Abstract: Steroidal saponins are a group of glycosides widely distributed among monocotyledonous families. They exert a wide spectrum of biological effects including cytotoxic and antitumor properties which are the most studied. This review is an update of our previous paper-Saponins as cytotoxic agents (Podolak et al. in Phytochem Rev 9:425-474, 2010) and covers studies that were since published (2010-2018). In this paper we refer to steroidal saponins presenting results of cytotoxicity studies, mechanisms of action an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 178 publications
(90 reference statements)
2
23
0
Order By: Relevance
“…Several studies reported that saponins have been proven to possess strong cytotoxicities. Saponins can activate the intrinsic or extrinsic apoptotic pathways, hold the cell cycle, autophagic dynamics, and inhibit angiogenesis and metastasis (Plaumann et al 1996;Sobolewska et al 2020). Podolak et al (2010) reported that the cytotoxic effects of saponins may be due to either apoptosis inducement or nonapoptotic cell death stimulation.…”
Section: A B C D a Bmentioning
confidence: 99%
“…Several studies reported that saponins have been proven to possess strong cytotoxicities. Saponins can activate the intrinsic or extrinsic apoptotic pathways, hold the cell cycle, autophagic dynamics, and inhibit angiogenesis and metastasis (Plaumann et al 1996;Sobolewska et al 2020). Podolak et al (2010) reported that the cytotoxic effects of saponins may be due to either apoptosis inducement or nonapoptotic cell death stimulation.…”
Section: A B C D a Bmentioning
confidence: 99%
“…[ 1 ] Both steroidal and triterpenoid saponins form an interesting class of compounds due to their pharmacological and biological properties und novel synthetic approaches are frequently reported. [ 2–5 ] In 1995, Yamasaki et al reported the isolation and characterization of two unusual triterpenoid saponins from the roots of Anemoclema glaucifolium (Ranunculaceae), a Chinese folk medicinal plant growing at altitudes between 1600 to 3000m in the Yangtse River valley region of China. [ 6 ] Accordingly named Anemoclemosides A and B, these saponins feature an unprecedented cyclic acetal linkage of the triterpene hederagenin to the carbohydrate l ‐arabinose in its open chain form rather than the typical glycosidic bond present in usual saponins.…”
Section: Methodsmentioning
confidence: 99%
“…Saponin are widely distributed in monocotyledonous families (Sobolewska et al, 2020), and several studies have confirmed that they have an extensive range of pharmacological activities. Steroidal saponins vernoniamyoside A, B, and B2, possess cytotoxicity activity against BT-549 (Wang et al, 2018), steroidal sapogenin 25-R-spirosta-3, 5-dien-12β-ol showed cytotoxicity on 5-8F cells a human nasopharyngeal carcinoma cell line (Chu et al, 2018).…”
Section: Quantitative Analysismentioning
confidence: 99%
“…Saponin subsides coronary heart disease (Yang et al, 2018) and acts as cytotoxic towards the human glioblastoma U87MG and U251 cell lines (Liu et al, 2018). Saponins like diosgenin have great value in the pharma industry and used as substrates in drug and steroid hormone production (Sobolewska et al, 2020). The presence of a high saponin amount might have contributed to the significant use of this plant in traditional medicine and drug discovery.…”
Section: Quantitative Analysismentioning
confidence: 99%
See 1 more Smart Citation